Whispering gallery mode excitation and collection using fused-tapered fiber tips - Zhu, Di (2013)
In this paper, we investigated whispering gallery mode (WGM) coupling in fused silica microspheres using fused-tapered fiber tips (FTFT). FTFT couplers are fabricated from single mode fibers using a standard splicing machine. FDTD simulation is first performed to demonstrate the feasibility of FTFT coupling to spherical WGM resonators. Two separate experiments are then conducted to characterize the performance of the coupler: one experiment measures the reflected signal from a single FTFT while the other adopts a two-FTFT coupling scheme and measures the transmission signal from a second FTFT. We obtained the comb-like eigenfrequency spectrum from both schemes. The measured free spectrum range (FSR) is around 2nm and the Q-factor is in the order of 105.